Odpowiedzi

2009-04-05T21:36:24+02:00
A)
0,3x = - 0,4
x=-4/10 * 10/3
x=-4/3
b)
x+2 - (2x-1) = 2
x+2-2x+1=2
-x=-1
x=1
c)
(1-5x) : 3 = (4x-3) : 2
2(1-5x)=3(4x-3)
2-10x=12x-9
-22x=-11
x=1/2
d)
(2x-5) : (3x+2) = ⅔
2(3x+2)=3(2x-5)
6x+4=6x-15
0=-19 sprzeczne
e)
(3x+2)² = (3x-1)(2+3x) /:(2+3x)
(3x+2)= (3x-1) sprzeczne

2
a)
M= 4-3ba
-3ba=M-4
a=(M-4)/-3b
b)
V= 2a / 5p+4
2a=V(5p+4)
a=V(5p+4)/2
c)
R(n-3a) = P
n-3a=P/R
-3a=(P/R)- n
a= -((P/R) -n)/3


2009-04-05T21:40:22+02:00
A) x=-4/3
b)x=1
c)x=1/2
d)brak rozwiązań
d) x=-2/3

a) a=(m-4)(-3b)
b)a=[V(5p+4)]/2
c)a=(P+Rn)/(-3R)